Translatability Of Arabic Fixed Expressions In Three Novels Into English Using Neural Machine Translation - Aldelaa, Abdullah Sanad Mohammad (2022)
Arabic fixed expressions (AFEs) have a symbolic figurative meaning that cannot be predicted from the individual components or the literal meanings of constituent parts. Many users nowadays rely on NMT systems to translate AFEs since these systems became an essential part of the process of translation. However, Neural Machine translation (NMT) creates a sort of difficulty and challenge to those who do not have enough experience in the translation of fixed expressions like proverbs and idioms. These translation systems might create a gap between Source Language (SL) and Target Language (TL). The study investigates the syntactic structure of the Arabic Fixed Expressions (AFEs), which allows a high level of accuracy to be achieved in its translation using selected Neural Machine Translation (NMT) systems. Also, this study seeks to identify the most efficient system to render the meaning of the (AFEs) extracted from the the three novels. Moreover, the study examines problems that hinder NMT systems when translating Arabic fixed expressions into English. In order to achieve the aim of this study, the researcher select samples of Arabic proverbs and idioms from three literary texts Banat AlRiyadh (Girls of AlRiyadh) by Rajaa Alsanea, Mawsim al-Hijrah ilâ al-Shamâl (Season of Migration to the North) and by Tayeb Saleh, and Suqut al-lmam (The Fall of the Imam) by Nawal El Saadawi) to be translated automatically by NMT systems in order to measure and evaluate the accuracy level of these software in particular. The researcher inserts texts containing a certain number of these expressions and analyze the obtained results after these systems translate the texts from Arabic into English.